Minimally Important Differences for Interpreting EORTC QLQ-C30 Scores in Patients With Advanced Breast Cancer. Issue 3 (4th June 2019) - Musoro, Jammbe Z; Coens, Corneel; Fiteni, Frederic; Katarzyna, Pogoda; Cardoso, Fatima; Russell, Nicola S; King, Madeleine T; Cocks, Kim; Sprangers, Mirjam Ag; Groenvold, Mogens; Velikova, Galina; Flechtner, Hans-Henning; et al.
Abstract: Background: We aimed to estimate the minimally important difference (MID) for interpreting group-level change over time, both within a group and between groups,  for the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire core 30 (EORTC QLQ-C30) scores in patients with advanced breast cancer. Methods: Data were derived from two published EORTC trials. Clinical anchors (eg, performance status [PS]) were selected using correlation strength and clinical plausibility of their association with a particular QLQ-C30 scale. Three change status groups were formed: deteriorated by one anchor category, improved by one anchor category, and no change. Patients with greater anchor changes were excluded. The mean change method was used to estimate MIDs for within-group change, and linear regression was used to estimate MIDs for between-group differences in change over time. For a given QLQ-C30 scale, MID estimates from multiple anchors were triangulated to a single value via a correlation-based weighted average. Results: MIDs varied by QLQ-C30 scale, direction (improvement vs deterioration), and anchor. MIDs for within-group change ranged from 5 to 14 points (improvement) and −14 to −4 points (deterioration), and MIDs for between-group change over time ranged from 4 to 11 points and from −18 to −4 points. Correlation-weighted MIDs for most QLQ-C30 scales ranged from 4 to 10 points in absolute values. Conclusions: Our findings aid interpretation of changes in EORTC QLQ-C30 scores over time, both within and between groups, and for performing more accurate sample size calculations for clinical trials in advanced breast cancer.